Pogo mad origami book 4 - Kumar, Ravi (BPI INDIA New Delhi, 2008)
Pogo Mad Origami Book 2 continues the creative journey into the art of paper folding with a fresh collection of innovative and fun origami designs. This book features clear, step-by-step instructions suitable for both beginners and experienced folders, encouraging creativity and dexterity. With a range of projects that inspire imagination, it serves as an excellent resource for enhancing origami skills while providing an enjoyable hands-on experience.